Personal Health and Wellness Practices of Negros Oriental High School Teachers - Pael, Kenneth B. (Silliman Journal, 2022)
The study aimed to determine the personal health and wellness practices of Negros Oriental High School teachers. The results of the study served as a basis for personal health improvement plans among the faculty. An adapted questionnaire was administered to 20 senior high school teachers. The findings of the study showed that as a group, the respondents have “good” physical functioning (mean = 78.75). Furthermore, the respondents also displayed “agreeable” responses to common health practices and behaviors (weighted mean = 2.84). The majority of the respondents also demonstrated adherence to good health practices.